Pengaruh Biaya Operasional Terhadap Laba Bersih PT. Ultrajaya Milk Industry & Trading Company, Tbk - Puji Muniarty; Angelia Putri Yuliani (LPPM Universitas Trunojoyo Madura, 2021)
This study aims to find out and analyze the effect of operating costs on net profit at PT Ultrajaya Milk Industri Trading Company, Tbk. Type of associative research with quantitative approach with the amount of population data for 29 years from 1990-2020, namely audited profit loss report in the form of operational costs and net profit and sampling techniques with purposive sampling for 15 years from 2005-2019. Data in the form of secondary data accessed through the company's official website and data analysis using operational cost and net profit analysis with documentation data collection techniques and library studies. Then continued with the analysis of operating costs and net profit and significance test (two tail test). The results showed that operational costs had a significant impact on net profit at PT. Ultrajaya Mik Industry Trading Company, Tbk.